100 great business ideas : from leading companies around the world - Kourdi, Jeremy. 4 0 16; 5 (London : Marshall Cavendish Business, 2009)
Presents one hundred business ideas, providing details about each idea and explaining steps to ensuring that these ideas are successful in practice.
Includes bibliographical references .
Adult.
Keywords: 2 -- 0; 6; Business planning. -- 20; 20; 2